Youth exclusion and empowerment in the contemporary global order : existentialities in migrations, identity and the digital space - Akanle, Olayinka (Emerald Publishing Limited, 2022)
The existential exclusion of youths from the mainframe of the current global order is an increasingly pressing issue. Research to date has proven youths struggle to survive and be relevant within current systemic and institutional arrangements, resulting in a major existential and generational problem. The second of two volumes filling a gap in the literature in understanding and responding to this grand challenge, this edited collection focuses particularly on the impact and complex consequences of migration, youth experiences and the functioning of digital spaces, and the shaping of youth identity through exposure to both. Addressing youth issues from around the world, Youth Exclusion and Empowerment in the Contemporary Global Order engages with practical, pragmatic, intellectual and policy perspectives. Delving into the lived experiences of young people in many countries, the chapters bring together a rich collection of research from diverse methodologies. Revealing how young people appear trapped, strategically excluded, and helplessly frustrated by the supposedly supportive institutional frameworks of society, the authors tackle this question: how can young people become empowered and socially active in this context? The original materials, literature and data collated across both volumes of Youth Exclusion and Empowerment in the Contemporary Global Order, addressing policy and practice issues for youth, present a cutting edge and innovative major contribution to the field of global youth studies.